Effect of different levels of nitrogen fertilizer on morphological and physiological parameters and nitrates accumulation of lettuce cultivars (Lactuca sativa L.) - M’hamdi, Mahmoud; Boughattas, Iteb; Chikh Rouhou, Hela; Souhli, E; Bettaieb, Taoufik (Research in Plant Biology, 2014)
The effect of nitrogen fertilizer level on growth and nitrate accumulation was studied in six lettuce cultivars (Lactuca sativa L.): ‘Batavia rouge’, ‘Vitalia’, ‘Great Laks’, ‘Type Beurre’, ‘Romaine’ and ‘Romaine LO3’. Three nitrogen levels: 0, 120 and 240 Kg.ha-1 was applied. During plant growth, agronomical parameters (root weight, fresh and dry matter, head diameter) and physiological parameters (nitrate concentration, chlorophyll fluorescence and sugar content) were evaluated. Results showed significant differences between cultivars and nitrogen treatment for the most agronomical and physiological parameters. The nitrogen treatment affects head weight and nitrate concentration in all cultivars; the cvs ‘Great Laks’ and ‘Type beurre’ accumulated respectively the less and high nitrate concentration. The highest nitrate concentration was recorded in external leaves whereas the lowest concentration was recorded in the central leaves for all cultivars. Furthermore, nitrate distribution and chlorophyll fluorescence on the leaves are closely related. This study revealed also correlation between root nitrate concentration, chlorophyll fluorescence and sugar content for all cultivars. This correlation depended on nitrogen fertilization level and the cultivar used.